Determinants of students deviant behavior in Nusa Bhakti Junior High School Semarang - Pangestika, Permata Ajeng; Arsal, Triwathy; Rachman, Maman (JESS (Journal of Educational Social Studies), 2022)
The efforts to build character and control student behavior are executed through the learning process and the application of school rules. Although learning activities and enforcing rules have been well pursued, in reality there are still many behavioral deviations committed by students. The research objectives are to identify forms of deviant behavior by students, analyze the factors that cause students to engage in deviant behavior and identify the types of parenting styles of students as well as school efforts in tackling students' deviant behavior. The data analysis technique used is qualitative data analysis with Merton's structural functional theory. Data collection is done by observation, in-depth interviews and documentation studies. The results showed that there were deviant behaviors executed by students of SMP Nusa Bhakti are smoking, drinking alcohol, and drug abuse. This deviant behavior is caused by the imperfect socialization process and the result of the socialization process of deviant sub-cultural values. The imperfect socialization process is influenced by students' family environmental factors, while the results of the socialization process of deviant sub-cultural values are influenced by environmental factors of peers, schools, communities and mass media. The efforts to overcome deviant behavior are executed by preventive, repressive, and curative methods.